2013
DOI: 10.1210/jc.2012-3842
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Changes in Testosterone Over Five Years in Community-Dwelling Men

Abstract: An age-related decline in T levels is not inevitable but is largely explained by smoking behavior and intercurrent changes in health status, particularly obesity and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
103
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(118 citation statements)
references
References 43 publications
12
103
2
1
Order By: Relevance
“…This is consistent with the findings that androgen status does not decline with aging among older men who remain in excellent (asymptomatic) health (45) although there is a decline associated with the co-morbidities of aging such as obesity, depression or cardiovascular disease. This is also consistent with the conclusions of other longitudinal studies (31,32). Nevertheless, our cross-sectional study cannot fully exclude that age itself, apart from co-morbidities, might also contribute to declines in age-related serum testosterone, DHT, and E 2 concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the findings that androgen status does not decline with aging among older men who remain in excellent (asymptomatic) health (45) although there is a decline associated with the co-morbidities of aging such as obesity, depression or cardiovascular disease. This is also consistent with the conclusions of other longitudinal studies (31,32). Nevertheless, our cross-sectional study cannot fully exclude that age itself, apart from co-morbidities, might also contribute to declines in age-related serum testosterone, DHT, and E 2 concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that testosterone plays an important role in metabolic activities, including the regulation of glucose and lipid metabolism (Aydilek and Aksakal 2005;Christoffersen et al 2010). Growing evidence has demonstrated that testosterone deficiency is associated with an increased incidence of obesity (Shi et al 2013;Stellato et al 2000). In addition, a positive correlation between obese-insulin resistance and testosterone deficiency has been reported (Grossmann et al 2008;Haffner et al 1994), but contradictory findings have been demonstrated in some animal models (Borst and Conover 2006;Erben et al 2000;Kakolewski et al 1968).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that testosterone replacement exerted beneficial effects on brain function, including the prevention of neuronal cell death, the balancing of brain oxidative stress and antioxidant activity, improvement of synaptic plasticity and the involvement of cognitive formation in animal models (Janowsky 2006, Meydan et al 2010, Filova et al 2013. Interestingly, growing evidence demonstrated that testosterone deficiency is associated with obese insulinresistance in men (Haffner et al 1994, Stellato et al 2000, Grossmann et al 2008, Shi et al 2013). All of those findings indicate that testosterone-deprivation can lead to obesity and cognitive decline.…”
Section: Introductionmentioning
confidence: 99%